2010
DOI: 10.1111/j.1398-9995.2009.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal allergic disease does not affect the phenotype of T and B cells or the immune response to allergens in neonates

Abstract: Our results suggest that maternal allergic disease has no effect on the neonatal response to allergens or the phenotype of neonatal lymphocytes. The factors studied here could, however, still affect later development of allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Understanding how the allergic response might change during pregnancy is critical if we are to elucidate how maternal disease impacts on fetal immune system development. A Th2-biased response to allergen seems to be retained in pregnancy: 1) pollen allergic women with detectable pollen-specific IgE have a Th2-skewed response to pollen allergens (Timothy grass/birch) [44]; and 2) allergenspecific and mitogen-induced IFN-γ decreases during pregnancy in atopic and nonatopic women, whereas allergen-specific IL-13 declines in nonatopic women only [45]. The relative blood eosinophilia that characterizes allergy also occurs in asthmatic pregnant women despite an apparent decline in eosinophil numbers during pregnancy [46].…”
Section: Impact Of Maternal Allergy On Immune Function During Pregnancymentioning
confidence: 99%
“…Understanding how the allergic response might change during pregnancy is critical if we are to elucidate how maternal disease impacts on fetal immune system development. A Th2-biased response to allergen seems to be retained in pregnancy: 1) pollen allergic women with detectable pollen-specific IgE have a Th2-skewed response to pollen allergens (Timothy grass/birch) [44]; and 2) allergenspecific and mitogen-induced IFN-γ decreases during pregnancy in atopic and nonatopic women, whereas allergen-specific IL-13 declines in nonatopic women only [45]. The relative blood eosinophilia that characterizes allergy also occurs in asthmatic pregnant women despite an apparent decline in eosinophil numbers during pregnancy [46].…”
Section: Impact Of Maternal Allergy On Immune Function During Pregnancymentioning
confidence: 99%
“…A recent study shows that the timothy- and birch-allergic mothers respond with increased proliferation and/or IL-4 production towards timothy and birch extract. However, cord blood mononuclear cell proliferation, phenotype of T cells, Foxp3(+) Tregs and B cells in response to the allergens are not affected by the allergic status of the mother [71]. Fetal exposures have been investigated as risk factors of early life allergic disease, and it is showed that nTreg levels during pregnancy in venous blood samples vary in association with both dog and cat exposure and atopic status [72].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have already tried to find some indications of future allergy development in cord blood. The responsiveness of cord blood cells of high-and low-risk children to allergens was followed [3,4], and polyclonal G + /Gbacteria stimulation [5][6][7][8] was tested. The proportion of both Th1 and Th2 cytokines in cord blood of high-and low-risk infants was tested [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%